GO membrane enhanced composite artificial gel periosteum material containing vascularized network and preparation method of GO membrane enhanced composite artificial gel periosteum material

By bio3D printing on the GO membrane-enhanced periosteal material, a vascularization pre-network is formed, and combined with mesoporous hydroxyapatite and bone marrow mesenchymal stem cells, the problem of difficult balance between biocompatibility and mechanical properties of traditional periosteal materials is solved, and multiple functions to promote angiogenesis and bone regeneration are achieved, and the regeneration and healing speed of bone tissue is improved.

CN119564923APending Publication Date: 2025-03-07LISHUI CENT HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411772042.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional periosteal materials have difficulty achieving an ideal balance between biocompatibility and mechanical properties, and lack of sufficient vascularization networks, resulting in limited bone tissue regeneration and healing speed.

Method used

A GO membrane-enhanced vascularized network composite artificial gel periosteum material was designed. By bio-3D printing on the base layer of the GO film composite gel, a composite gel surface layer with a vascularized prenetwork was formed, combining mesoporous hydroxyapatite and bone marrow mesenchymal stem cells to promote angiogenesis and bone regeneration.

Benefits of technology

It achieves multiple functions of promoting angiogenesis and bone regeneration while maintaining appropriate strength, improves the regeneration and healing speed of bone tissue, and is suitable for the repair of large segments of bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564923A_ABST
    Figure CN119564923A_ABST
Patent Text Reader

Abstract

The invention discloses a GO membrane enhanced composite artificial gel periosteum material containing a vascularized network and a preparation method of the GO membrane enhanced composite artificial gel periosteum material. Comprising the following steps: 1) preparing multiple layers of GO films by adopting a circulating blade coating-drying method; 2) placing the GO film in a convex array mold, pouring an HAMA solution, and carrying out UV curing to obtain a GO film composite gel substrate layer; (3) preparing an HAMA solution containing dopamine-coated mesoporous hydroxyapatite loaded with an angiogenesis promoting factor; 4) preparing a gelatin / HAMA mixed solution by using a blood vessel differentiation promoting culture medium as a solvent, and adding the bone marrow mesenchymal stem cells; and (5) performing 3D printing on the solution in the steps (3) and (4) on the uneven surface of the GO film composite gel substrate layer according to a drawing, performing UV curing, and performing in-vitro angiogenesis culture at 37 DEG C to obtain the composite artificial gel periosteum containing the vascularized network. The periosteum material is printed with the vascularized network in situ, and is compounded with the GO film with the function of enhancing and promoting osteogenesis, so that innovation of the periosteum material is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bone repair and periosteum preparation, and relates to an artificial periosteum material and a preparation method thereof, and in particular to a GO membrane-enhanced vascularized network-containing composite artificial gel periosteum material and a preparation method thereof. Background Art

[0002] Repair and regeneration of bone damage is a major challenge in clinical medicine, especially when dealing with complex fractures and large bone defects. Traditional treatments such as internal fixation and external fixation, although effective, cannot fully meet clinical needs in some cases.

[0003] In recent years, with the rapid development of biomaterials science, tissue engineering and regenerative medicine, bone repair technology has made significant progress. New biomaterials such as calcium phosphate ceramics and bioglass are widely used to fill and support bone defects and promote bone regeneration. The advancement of periosteum technology has also played an important role in bone regeneration, further supporting the bone repair process by enhancing or reconstructing periosteum function. The combined application of these technologies provides a more effective treatment option for patients with bone injuries, significantly improving the rehabilitation effect and quality of life of patients.

[0004] Traditional periosteal materials have difficulty in achieving an ideal balance between biocompatibility and mechanical properties. The materials may be too rigid or not strong enough to effectively support the growth and healing of bone tissue. In addition, these materials usually lack sufficient vascularization networks, resulting in limited delivery of nutrients and oxygen, which seriously affects the regeneration and healing rate of bone tissue. The problem of single function also exists significantly. Many existing materials only provide mechanical support or simple biological activity, and cannot simultaneously achieve the multiple functions of promoting angiogenesis and bone regeneration.

[0005] In view of the above problems, the present invention designs a GO membrane-enhanced vascularized network composite artificial gel periosteum material and its preparation method. The periosteum material is composed of a GO film layer and a HAMA gel layer as a mixed gel base, and a HAMA solution containing dopamine-coated mesoporous hydroxyapatite loaded with angiogenic growth factors and a gelatin / HAMA mixed solution loaded with bone marrow mesenchymal stem cells are printed on its surface, so that the periosteum structure has multiple functions of promoting angiogenesis and bone regeneration while maintaining appropriate strength. Summary of the invention

[0006] The purpose of the present invention is to provide a GO membrane-enhanced vascularized network composite artificial gel periosteum material and a preparation method thereof in view of the deficiencies in the prior art.

[0007] The present invention is implemented by the following technical solutions:

[0008] A method for preparing a GO membrane-enhanced vascularized network composite artificial gel periosteum material comprises the following steps:

[0009] 1) adding graphene oxide GO into a co-solvent of ethanol and water to obtain a coating solution, and preparing a multilayer GO film by a cyclic coating-drying method;

[0010] 2) placing the GO film in a protrusion array mold, pouring a methacrylamide hyaluronic acid HAMA solution, and immersing the GO film in the solution, and performing UV curing to obtain a GO film composite gel substrate layer with a flat surface on one side and a protrusion array morphology on the other side;

[0011] 3) preparing mesoporous hydroxyapatite, and loading angiogenesis promoting factors to obtain drug-loaded mesoporous hydroxyapatite, coating it with dopamine, adding HAMA solution, and mixing to obtain a matrix solution;

[0012] 4) using angiogenic differentiation medium as a solvent to prepare a gelatin / HAMA mixed solution, and adding bone marrow mesenchymal stem cells to obtain angiogenic solution;

[0013] 5) According to the required drawings, bio-3D printing is performed on the raised array surface of the GO film composite gel base layer using the solution obtained in steps 3) and 4) as the printing material, wherein the vascularization-promoting solution is used as the vascular network printing material and the matrix solution is used as the matrix printing material. The printing and UV curing are performed to form a composite gel surface layer with a vascularized pre-network, and angiogenesis is cultured in vitro at 37°C to obtain a composite artificial gel periosteum containing a vascularized network.

[0014] In the above technical solution, further, in step 1), the GO concentration in the coating liquid is 0.05-0.1wt%, and the volume ratio of ethanol to water is 1:9-1:7; the thickness of the GO film is controlled to be 50-200μm. The GO is preferably a sheet with a size of about 3-8μm, and the coating liquid is dried at 50-60°C after coating, and the coating and drying are repeated several times.

[0015] Furthermore, in step 2), the HAMA solution has a concentration of 5-7.5 wt %, and a photoinitiator is added with a concentration of 0.1-0.25 wt %.

[0016] In the present invention, the photoinitiator can be one or more of LAP, Irgacure, and I2959. The thickness of the protrusion array mold is usually 400-800 μm. The UV curing light source is a 350-410 nm UV light source with a power of 20-40 mW / cm 2According to a specific example of the present invention, a groove array structure may be provided in the protrusion array mold, the grooves are 200-400 μm long, 200-400 μm wide, 50-200 μm high, and 200-300 μm apart, so that a corresponding protrusion array can be formed on one surface after the material is demoulded.

[0017] Furthermore, in step 3), the preparation method of the mesoporous hydroxyapatite is: mixing a phosphate ion solution, a calcium-containing solution, a surfactant and a template solution, adjusting the pH to 9-11, aging at 35-40°C, collecting the precipitate by centrifugation after aging and repeatedly washing it with deionized water and ethanol, and drying the obtained product at 50-80°C until the mass is constant to obtain a mesoporous hydroxyapatite material.

[0018] Furthermore, the concentration of phosphate ions in the mixed solution is in the range of 0.25-0.35 M, the concentration of calcium is 0.45-0.55 M, the surfactant is one of phytic acid, SDS, EDTA or citric acid, and the amount added is 4-6 (w / v)% of the total solution, the template solution selected is one of F127 or CTAB, the concentration is 0.1-0.4 g / ml, and the centrifugal speed is 5000-10000 rpm / min.

[0019] Furthermore, the preparation method of the matrix solution is: using a cyclic ultrasound-freeze-drying loading method to load angiogenic factors in the pores of mesoporous hydroxyapatite, then immersing the obtained mesoporous hydroxyapatite in a dopamine solution to adjust the pH, in situ polymerizing on its surface to form a polydopamine polymer coating layer, the concentration of the obtained mesoporous hydroxyapatite is preferably 3-5wt%, and the obtained material is then added to a HAMA solution containing a photoinitiator and mixed, and the concentration of the obtained material in the solution is preferably 1-3wt%; wherein the cyclic ultrasound-freeze-drying loading method is to add the mesoporous hydroxyapatite to a PBS solution containing angiogenic factors, the concentration of the mesoporous hydroxyapatite is preferably 2-5wt%, and then vacuum freeze-drying is performed after ultrasonic treatment, and the loading is repeated several times.

[0020] Furthermore, the loaded angiogenic growth factor is one or more of VEGF, TGF-β, FGF and PDGF, and the corresponding concentrations are 10-100 ng / mL, 1-10 ng / mL, 1-50 ng / mL and 1-50 ng / mL, respectively; the ultrasonic power is 80-100 W, the frequency is 20-40 kHz, and after each ultrasonic loading, it is freeze-dried for 2-10 hours under the conditions of vacuum degree 50-100 Pa and -20--40°C, and the ultrasonic loading and freeze-drying process is repeated 3-5 times; the dopamine solution concentration is 6-16 mg / mL, the pH value is adjusted to 8.5-11, the reaction is performed for 4-8 hours, and after washing, it is freeze-dried for 2-10 hours under the conditions of vacuum degree 50-100 Pa and -20--40°C to obtain dopamine-encapsulated mesoporous hydroxyapatite loaded with angiogenic factors; the HAMA solution concentration is 3-5wt%, wherein the photoinitiator concentration is 0.1-0.25wt%.

[0021] Furthermore, in the gelatin / HAMA solution, the HAMA concentration is 0.1-0.5wt%, the solution contains a photoinitiator with a concentration of 0.1-0.25wt%, and the gelatin concentration is 1-15wt%; the added bone marrow mesenchymal stem cells have a density of 1-3×10 7 / mL, and the generations used were P2-P5.

[0022] Furthermore, the angiogenic differentiation medium is a basal medium doped with angiogenic factors: the basal medium used is one of M199 basal medium, mixed medium DMEM / F12 and RPMI 1640, and the angiogenic factors used are one or more of VEGF, bFGF, IGF, and the corresponding concentrations are usually 10-20ng / mL, 5-10ng / mL, 10-20ng / mL.

[0023] Furthermore, the diameter of the 3D printed vascularized network structure is 50-100 μm, the substrate thickness is 100-300 μm, and the wavelength of the printing and UV curing light source is 405 nm and the power is 20 W / m 2 , exposure time is 30s;

[0024] Furthermore, in the in vitro angiogenic culture, the basal culture medium used is one of M199 basal culture medium, mixed culture medium DMEM / F12 and RPMI 1640, and the angiogenic factors used are one or more of VEGF, bFGF, IGF, and the corresponding concentrations are usually 10-20ng / mL, 5-10ng / mL, 10-20ng / mL; and the culture is carried out in an incubator at 37°C and 5% CO2 for 7-14 days.

[0025] A GO membrane-reinforced vascularized network composite artificial gel periosteum material prepared by any of the methods described above.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1) The present invention uses HAMA, GO, mesoporous hydroxyapatite and the like as raw materials, and combines cyclic scraping-drying method, casting method, UV in-situ photocuring, cyclic ultrasound-freeze-drying loading, in-situ self-polymerization, biological 3D photocuring printing, thermal sacrifice and other combined processes to prepare a GO membrane-enhanced vascularized network composite artificial gel periosteum material.

[0028] 2) The artificial gel periosteum material in the present invention is provided with a multiple composite structure: the inner side is a flat HAMA layer, the first intermediate layer is a GO membrane reinforcement layer, the second intermediate layer is a HAMA layer with a protrusion array, and the outer layer is a vascularized network composite gel layer. The inner HAMA layer is a flat gel layer, and the thickness of the artificial gel periosteum material is relatively low, which can form a good fit with the bone; the first intermediate layer is a GO membrane material pressed by overlapping layers of GO sheets, which has high mechanical strength and is placed in the middle of the artificial gel periosteum for the purpose of mechanical enhancement; the second intermediate layer forms a non-flat structure on the surface by a mold method, so as to improve the interface bonding effect during the subsequent 3D printing of the outer layer; the outer layer is a HAMA layer provided with a vascularized network and loaded with bone marrow mesenchymal stem cells. The organic synergy of the above four-layer composite structure from the inside to the outside enables the artificial gel periosteum in the present invention to meet the requirements for efficient repair of large bone defects under the condition of periosteum loss.

[0029] 3) In the present invention, the in-situ establishment of a vascularized network is achieved through multiple structural settings. The vascularized network part is mainly located in the outer layer of the artificial gel periosteum. The gel layer structure containing the cell-loaded gelatin / HAMA network structure is formed by biological 3D printing technology. Subsequently, during the in vitro angiogenesis culture process at 37°C, the gelatin forms a pore structure for vascularization in the HAMA gel matrix based on the thermal sacrificial properties. When the above-mentioned artificial gel periosteum material induces the formation of a vascularized network in vitro, the gelatin is first thermally sacrificed to form a spatial pore structure, providing a reticular space for the formation of a vascularized network structure; due to the use of angiogenic culture medium as a solvent, the bone marrow mesenchymal stem cells in the pore structure proliferate, migrate and differentiate; at the same time, the mesoporous hydroxyapatite loaded with angiogenic factors in the HAMA matrix continuously releases angiogenic factors for a long time, further promoting the induction and regulation of stem cell angiogenesis differentiation, and finally making the vascularized network perfectly formed. The above-mentioned vascularized network preset strategy in vitro and its transfer to the artificial material matrix are of great significance for the treatment of large bone defects.

[0030] 4) The composite artificial gel periosteum material in the present invention has the functions of promoting blood vessels, promoting osteogenesis, and high mechanical strength. Among them, the multiple promoting blood vessels functions realize the in vitro generation of vascularized network structures from the perspectives of physics (spatial pore structure) and chemistry (promoting angiogenesis differentiation culture medium and promoting angiogenesis growth factors), and simulate the physiological characteristics of rich vascularization of natural periosteum in a consistent manner, providing sufficient oxygen and nutrients for subsequent osteogenesis; in this field, vascularization has excellent synergistic osteogenic functions, and combined with the degradation of mesoporous hydroxyapatite, it continuously releases calcium ions, phosphate ions and other essential components for osteogenesis, and doubles the effect of promoting osteogenesis, ensuring good repair effects for large bone defects; the GO film in the basal layer provides sufficient strength for the entire periosteum, serving as an attachment layer for gel casting and attachment, and when the gel is degraded, the exposed internal GO can further promote osteogenesis; the above functions directly cooperate with each other, providing excellent conditions for bone regeneration and bone repair.

[0031] 5) In the present invention, in order to address the phenomenon that bone tissue dies due to insufficient blood supply and insufficient nutrient exchange during bone regeneration and bone repair, an innovative casting method is used to cast a protrusion array mold to form a protrusion columnar structure, and then gel printing is filled in the gaps between adjacent protrusions to induce the formation of a vascular network. In addition, after gelatin is thermally sacrificed under vascularized culture conditions, a spatial pore structure is further formed in the gel matrix. This type of structure is not only conducive to nutrient exchange, but also synergistic with angiogenic factors, and is also conducive to the formation of microvessels in small holes of bone marrow mesenchymal stem cells. The generation of this type of blood supply can provide good material exchange for bone defect structures of greater thickness and area for a long time, thereby meeting the needs of large-area bone repair.

[0032] 6) The dopamine-coated mesoporous hydroxyapatite loaded with angiogenic growth factors in the present invention adopts the innovative idea of ​​"three uses in one body", and uses the osteogenic effect of hydroxyapatite itself and the strong adsorption of angiogenic factors in its mesoporous structure to support long-term osteogenesis and angiogenic differentiation through the sustained release effect of the mesoporous structure; in order to further improve its biocompatibility, a large amount of polydopamine is also attached to the surface of hydroxyapatite. This type of dopamine-coated mesoporous hydroxyapatite loaded with angiogenic growth factors is a new upgrade of the old process, and its unique function of "three uses in one body" plays an important role in the present invention.

[0033] 7) The artificial gel periosteum material in the present invention is prepared by a combination of processes such as cyclic scraping-drying method, casting method, UV in-situ photocuring, cyclic ultrasound-freeze-drying loading, in-situ self-polymerization, biological 3D photocuring printing, and thermal sacrifice. A multi-layer GO membrane is prepared by the cyclic scraping-drying method, and the combination of blending and casting methods obtains a GO thin film composite gel base layer with a flat side and a protruding array morphology on the other side; the cyclic ultrasound-freeze-drying loading, in-situ self-polymerization, and biological 3D printing technologies jointly realize the precursor construction of the surface vascularized network; finally, with the technical support of gelatin thermal sacrifice and in vitro culture, a GO membrane-enhanced composite artificial gel periosteum material containing a vascularized network is successfully constructed. Based on clinical needs and material preparation requirements, the present invention cleverly selects the above-mentioned processes, and combines experiments to realize the organic combination of the above-mentioned processes, and finally meets the material preparation requirements and successfully obtains the corresponding materials.

[0034] 8) The GO membrane-enhanced vascularized network composite artificial gel periosteum material of the present invention can be prepared by customizing molds according to the needs of patients, and has versatility, ease of use and practicality, and can meet the different needs of various patients. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A schematic diagram of the preparation process of the GO membrane-enhanced vascularized network composite artificial gel periosteum material of the present invention;

[0036] Figure 2 This is a photo of a multilayer GO film (including bending and twisting states);

[0037] Figure 3 This is a photo of mesoporous hydroxyapatite;

[0038] Figure 4 The survival of the GO membrane-enhanced composite artificial gel periosteum material containing a vascularized network and bone marrow mesenchymal stem cells after culture;

[0039] Figure 5 The results are the differentiation results of cells after 14 days of culture in the GO membrane-enhanced vascularized network composite artificial gel periosteum material of the present invention. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0041] Comparative Example 1:

[0042] 1) Using GO sheets with a size of 5 μm, a mixed solvent with an ethanol / water volume ratio of 1:8 was prepared, and then GO with a concentration of 0.05 wt% was added to obtain a GO coating solution; then the above solution was evenly coated on the center of the mold, and then open-dried in a drying oven at 60°C, repeated 5 times, and a GO film with a thickness of 80 μm was obtained in the center of the mold.

[0043] 2) In a light-proof condition and a 42°C water bath, a 5wt% HAMA solution was prepared using a PBS solvent containing 0.25wt% LAP. A layer of HAMA solution was first poured into a casting mold (a groove array structure was provided in the casting mold, and the grooves were 400μm long, 400μm wide, 300μm high, and 300μm apart). Then, the GO film was laid flat, and then the remaining HAMA solution was poured. A 410nm UV light source (power of 20mW / cm 2 ), the irradiation time was 120s, and finally a GO thin film composite gel substrate layer with one side being flat and the other side having a protrusion array morphology was formed, and the thickness of the composite gel layer was 200μm.

[0044] 3) Phytic acid was used as a surfactant (5 (w / v)%) and CTAB was used as a template (concentration of 0.2 g / ml), phosphate and calcium salt solutions were added thereto, the concentrations were 0.3 M and 0.5 M respectively, the pH of the solution was adjusted to 9 and then aged at 37°C for 24 hours; the aged product was centrifuged at 5000 rpm / min, washed and dried in an oven at 60°C to constant weight to obtain mesoporous hydroxyapatite. 3 wt% mesoporous hydroxyapatite was placed in a PBS solution containing 10 ng / mL VEGF and 1 ng / mL FGF, and ultrasonic loading was performed using 100 W power and 20 kHz power; then freeze-dried at a vacuum degree of 50 Pa and -40°C for 6 hours, and the above process was repeated 3 times. Subsequently, the mesoporous hydroxyapatite loaded with the above-mentioned angiogenic growth factor was added to a dopamine solution with a concentration of 8 mg / mL at a concentration of 3 wt%, the pH was adjusted to 8.5, and the dopamine was allowed to self-polymerize on the surface of the mesoporous hydroxyapatite for 4 h, followed by washing and freeze-drying. Under light-proof conditions, the dopamine-encapsulated mesoporous hydroxyapatite loaded with angiogenic growth factor was added to a 5 wt% HAMA / PBS solution (42°C, containing 0.25 wt% LAP initiator) at a concentration of 3 wt%, and the composite HAMA solution was prepared after oscillation and mixing. Subsequently, mature bone marrow mesenchymal stem cells (density of 3×10 7 / mL) was added to the above solution to obtain a matrix solution.

[0045] 4) Using a HAMA solution containing bone marrow mesenchymal stem cells and dopamine-encapsulated mesoporous hydroxyapatite loaded with angiogenic growth factors, that is, the matrix solution was bio-3D printed on the side of the GO film composite gel layer with a protruding array morphology, with a printing thickness of 300 μm. After printing, cultured in RPMI1640 medium containing 20 ng / mL VEGF and 20 ng / mL IGF for 14 days.

[0046] 5) The artificial gel periosteum was bent and folded 5 times without any rupture; after 14 days of culture, the material was sliced ​​and stained for live and dead, and it was found that the survival rate of mesenchymal stem cells in this area was about 67%; ALP staining showed that the area stained dark purple exceeded 40%, indicating that there was a certain osteoblast activity in this area; Von Kossa staining found that there was a small amount of dark brown deposits, indicating a certain mineralization. The part with vascular network was stained with vWF, and it was found that there was almost no punctate fluorescence, indicating that almost no vascular structure was formed. The above-mentioned artificial gel periosteum was wrapped on the surface of natural bone and implanted into a large bone defect model in rats. After 4 weeks, the Micro-CT results showed that the bone repair effect was general.

[0047] Embodiment 1:

[0048] 1) Using GO sheets with a size of 5 μm, a mixed solvent with an ethanol / water volume ratio of 1:8 was prepared, and then GO with a concentration of 0.05 wt% was added to obtain a GO coating solution; then the above solution was evenly coated on the center of the mold, and then open-dried in a drying oven at 60°C, repeated 5 times, and a GO film with a thickness of 80 μm was obtained in the center of the mold.

[0049] 2) In a light-proof condition and a 42°C water bath, a 5wt% HAMA solution was prepared using a PBS solvent containing 0.25wt% LAP. A layer of HAMA solution was first poured into a casting mold (a groove array structure was provided in the casting mold, and the grooves were 400μm long, 400μm wide, 300μm high, and 300μm apart). Then, the GO film was laid flat, and then the remaining HAMA solution was poured. A 410nm UV light source (power of 20mW / cm 2 ), the irradiation time was 120s, and finally a GO thin film composite gel substrate layer with one side being flat and the other side having a protrusion array morphology was formed, and the thickness of the composite gel layer was 200μm.

[0050] 3) Phytic acid was used as a surfactant (5 (w / v)%) and CTAB was used as a template (concentration of 0.2 g / ml), phosphate and calcium salt solutions were added thereto, the concentrations were 0.3 M and 0.5 M respectively, the pH of the solution was adjusted to 9 and then aged at 37°C for 24 hours; the aged product was centrifuged at 5000 rpm / min, washed and dried in an oven at 60°C to constant weight to obtain mesoporous hydroxyapatite. 3 wt% mesoporous hydroxyapatite was placed in a PBS solution containing 10 ng / mL VEGF and 1 ng / mL FGF, and ultrasonic loading was performed using 100 W power and 20 kHz power; then freeze-dried at a vacuum degree of 50 Pa and -40°C for 6 hours, and the above process was repeated 3 times. Then, the mesoporous hydroxyapatite loaded with the above-mentioned angiogenic growth factor was added to a dopamine solution with a concentration of 8 mg / mL at a concentration of 3 wt%, the pH was adjusted to 8.5, and the dopamine was allowed to self-polymerize on the surface of the mesoporous hydroxyapatite for 4 hours, followed by washing and freeze-drying. Under light-proof conditions, the dopamine-encapsulated mesoporous hydroxyapatite loaded with angiogenic growth factor was added to a 5 wt% HAMA / PBS solution (42° C., containing 0.25 wt% LAP initiator) at a concentration of 3 wt%, and the composite HAMA solution was obtained after oscillation and mixing, thereby obtaining a matrix solution.

[0051] 4) In a dark place and at 45°C water bath, a mixed solution of HAMA concentration of 0.1wt% (containing 0.1wt% LAP) and gelatin concentration of 15wt% was prepared, and the solvent was angiogenic differentiation medium; then, mature bone marrow mesenchymal stem cells of generation P3 (density of 3×10 7 / mL) was added to the above solution to obtain angiogenic solution.

[0052] 5) Using the HAMA solution containing dopamine-encapsulated mesoporous hydroxyapatite loaded with angiogenic growth factors, i.e., the matrix solution, as the matrix printing material, and the HAMA / gelatin solution loaded with bone marrow mesenchymal stem cells, i.e., the angiogenic solution, as the vascular network printing material, a gel surface layer containing a pre-vascularized network was bio-3D printed on the side of the GO film composite gel substrate layer with a protruding array morphology, with a printing thickness of 300 μm. After printing, the gel surface layer was cultured at 37°C in RPMI 1640 medium containing 20 ng / mL VEGF and 20 ng / mL IGF for 14 days.

[0053] 6) Compared with Comparative Example 1, a vascularized network was formed on the surface of the basal layer of the GO film composite gel by biological 3D printing. The artificial periosteum was bent and folded 5 times without rupture; after 14 days of culture, the material was sliced ​​and stained for live and dead, and it was found that the survival rate of mesenchymal stem cells in this part was greater than 85%; ALP staining was used to find that the area stained dark purple exceeded 60%, indicating strong osteoblast activity in this part; Von Kossa staining found that there were continuous and intermittent dark brown deposits, indicating good mineralization. The part with the vascular network was stained with vWF, and sparse dot-like fluorescence was found, indicating that the vascular network structure was differentiated. The above-mentioned artificial gel periosteum was wrapped on the surface of natural bone and implanted into a large bone defect model in rats. After 4 weeks, the Micro-CT results showed that it had a good bone repair effect.

[0054] Embodiment 2:

[0055] 1) In a light-proof condition and a 42°C water bath, a 5 wt% HAMA solution was prepared using a PBS solvent containing 0.25 wt% LAP. The HAMA solution was first poured into a casting mold (a groove array structure was provided in the casting mold, with a groove length of 400 μm, a width of 400 μm, a height of 300 μm, and a spacing of 300 μm). A 410 nm UV light source (power of 20 mW / cm 2 ), the irradiation time is 120s, and finally a gel base layer with one side being flat and the other side having a protrusion array morphology is formed, and the thickness of the gel base layer is 200μm.

[0056] 3) Phytic acid was used as a surfactant (5 (w / v)%) and CTAB was used as a template (concentration of 0.2 g / ml), phosphate and calcium salt solutions were added thereto, the concentrations were 0.3 M and 0.5 M respectively, the pH of the solution was adjusted to 9 and then aged at 37°C for 24 hours; the aged product was centrifuged at 5000 rpm / min, washed and dried in an oven at 60°C to constant weight to obtain mesoporous hydroxyapatite. 3 wt% mesoporous hydroxyapatite was placed in a PBS solution containing 10 ng / mL VEGF and 1 ng / mL FGF, and ultrasonic loading was performed using 100 W power and 20 kHz power; then freeze-dried at a vacuum degree of 50 Pa and -40°C for 6 hours, and the above process was repeated 3 times. Then, the mesoporous hydroxyapatite loaded with the above-mentioned angiogenic growth factor was added to a dopamine solution with a concentration of 8 mg / mL at a concentration of 3 wt%, the pH was adjusted to 8.5, and the dopamine was allowed to self-polymerize on the surface of the mesoporous hydroxyapatite for 4 hours, followed by washing and freeze-drying. Under light-proof conditions, the dopamine-encapsulated mesoporous hydroxyapatite loaded with angiogenic growth factor was added to a 5 wt% HAMA / PBS solution (42° C., containing 0.25 wt% LAP initiator) at a concentration of 3 wt%, and the composite HAMA solution was obtained after oscillation and mixing, thereby obtaining a matrix solution.

[0057] 4) In a dark place and at 45°C water bath, a mixed solution of HAMA concentration of 0.1wt% (containing 0.1wt% LAP) and gelatin concentration of 15wt% was prepared, and the solvent was angiogenic differentiation medium; then, mature bone marrow mesenchymal stem cells of generation P3 (density of 3×10 7 / mL) was added to the above solution to obtain angiogenic solution.

[0058] 5) Using the HAMA solution containing dopamine-encapsulated mesoporous hydroxyapatite loaded with angiogenic growth factors, that is, the matrix solution, as the matrix printing material, and the HAMA / gelatin solution loaded with bone marrow mesenchymal stem cells, that is, the angiogenic solution, as the vascular network printing material, the side of the gel basal layer with the convex array morphology was subjected to biological 3D printing of the gel surface layer containing the pre-vascularized network, and the printing thickness was 300 μm. After printing, the cells were cultured at 37°C in RPMI 1640 medium containing 20 ng / mL VEGF and 20 ng / mL IGF for 14 days.

[0059] 6) Compared with Example 1, the GO film composite is reduced. The artificial periosteum was bent and folded twice and then ruptured; after 14 days of culture, the material was sliced ​​and stained for live and dead, and it was found that the survival rate of mesenchymal stem cells in this part was greater than 82%; ALP staining was used to find that the area stained dark purple exceeded 55%, indicating that the osteoblast activity in this part was strong; VonKossa staining found that there were continuous and intermittent dark brown deposits, indicating good mineralization. The part with vascular network was stained with vWF, and sparse dot-like fluorescence was found, indicating that the vascular network structure was differentiated. The above-mentioned artificial gel periosteum was wrapped on the surface of natural bone, but it was partially ruptured during the wrapping process and implanted into a large bone defect model in rats. After 4 weeks, the Micro-CT results showed that the bone repair effect was between Example 1 and Comparative Example 1.

[0060] Embodiment 3:

[0061] 1) Using GO sheets with a size of 5 μm, a mixed solvent with an ethanol / water volume ratio of 1:8 was prepared, and then GO with a concentration of 0.05 wt% was added to obtain a GO coating solution; then the above solution was evenly coated on the center of the mold, and then open-dried in a drying oven at 60°C, repeated 5 times, and a GO film with a thickness of 80 μm was obtained in the center of the mold.

[0062] 2) In a dark environment and a 42°C water bath, a 5 wt% HAMA solution was prepared using 0.25 wt% LAP in PBS solvent. A layer of HAMA solution was first poured into a casting plate mold, and then the GO film was laid flat, and then the remaining HAMA solution was poured. A 410 nm UV light source (power of 20 mW / cm 2 ), the irradiation time was 120s, and finally a GO thin film composite gel substrate layer with smooth two sides was formed, and the thickness of the composite gel layer was 200μm.

[0063] 3) Phytic acid was used as a surfactant (5 (w / v)%) and CTAB was used as a template (concentration of 0.2 g / ml), phosphate and calcium salt solutions were added thereto, the concentrations were 0.3 M and 0.5 M respectively, the pH of the solution was adjusted to 9 and then aged at 37°C for 24 hours; the aged product was centrifuged at 5000 rpm, washed and dried in an oven at 60°C to constant weight to obtain mesoporous hydroxyapatite. 3 wt% mesoporous hydroxyapatite was placed in a PBS solution containing 10 ng / mL VEGF and 1 ng / mL FGF, and ultrasonic loading was performed using a power of 100 W and a power of 20 kHz; then freeze-dried at a vacuum of 50 Pa and -40°C for 6 hours, and the above process was repeated 3 times. Then, the mesoporous hydroxyapatite loaded with the above-mentioned angiogenic growth factor was added to a dopamine solution with a concentration of 8 mg / mL at a concentration of 3 wt%, the pH was adjusted to 8.5, and the dopamine was allowed to self-polymerize on the surface of the mesoporous hydroxyapatite for 4 hours, followed by washing and freeze-drying. Under light-proof conditions, the dopamine-encapsulated mesoporous hydroxyapatite loaded with angiogenic growth factor was added to a 5 wt% HAMA / PBS solution (42° C., containing 0.25 wt% LAP initiator) at a concentration of 3 wt%, and the composite HAMA solution was obtained after oscillation and mixing, thereby obtaining a matrix solution.

[0064] 4) In a dark place and at 45°C water bath, a mixed solution of HAMA concentration of 0.1wt% (containing 0.1wt% LAP) and gelatin concentration of 15wt% was prepared, and the solvent was angiogenic differentiation medium; then, mature bone marrow mesenchymal stem cells of generation P3 (density of 3×10 7 / mL) was added to the above solution to obtain angiogenic solution.

[0065] 5) Using the HAMA solution containing dopamine-encapsulated mesoporous hydroxyapatite loaded with angiogenic growth factors, i.e., the matrix solution, as the matrix printing material, and the above-mentioned HAMA / gelatin solution loaded with bone marrow mesenchymal stem cells, i.e., the angiogenic solution, as the vascular network printing material, a gel surface layer containing a pre-vascularized network was bio-3D printed on the surface of the GO film composite gel layer, with a printing thickness of 300 μm. After printing, the cells were cultured in RPMI 1640 medium containing 20 ng / mL VEGF and 20 ng / mL IGF at 37°C for 14 days.

[0066] 6) Compared with Example 1, a flat mold was used for casting, that is, a flat surface was used to replace the protruding array morphology on one side of the GO film composite gel base layer. The artificial periosteum was bent and folded 5 times without any rupture, but the surface layer of the gel containing the vascularized network printed by the surface biological 3D printing and the GO film composite gel base layer were separated during the second bending test; after 14 days of culture, the material was sliced ​​and stained for live and dead, and it was found that the survival rate of mesenchymal stem cells in this part was greater than 81%; ALP staining was used to find that the area stained dark purple exceeded 62%, indicating that the osteoblast activity in this part was strong; Von Kossa staining found that there were continuous and intermittent dark brown deposits, indicating good mineralization. The part with vascular network was stained with vWF, and sparse dot-like fluorescence was found, indicating that there was differentiation of vascularized structure. The above-mentioned artificial gel periosteum was wrapped on the surface of natural bone and implanted into a large bone defect model in rats. After 4W, the Micro-CT results showed that the bone repair effect was close to that in Example 1.

[0067] The above-described embodiments are only some of the preferred solutions of the present invention, but they are not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing a GO membrane-enhanced vascularized network composite artificial gel periosteum material, characterized in that: The following steps are involved: 1) adding graphene oxide GO into a co-solvent of ethanol and water to obtain a coating solution, and preparing a multilayer GO film by a cyclic coating-drying method; 2) placing the GO film in a protrusion array mold, pouring a methacrylamide hyaluronic acid HAMA solution, and immersing the GO film in the solution, and performing UV curing to obtain a GO film composite gel substrate layer with a flat surface on one side and a protrusion array morphology on the other side; 3) preparing mesoporous hydroxyapatite, and loading angiogenesis promoting factors to obtain drug-loaded mesoporous hydroxyapatite, coating it with dopamine, adding HAMA solution, and mixing to obtain a matrix solution; 4) using angiogenic differentiation medium as a solvent to prepare a gelatin / HAMA mixed solution, and adding bone marrow mesenchymal stem cells to obtain angiogenic solution; 5) According to the required drawings, bio-3D printing is performed on the raised array surface of the GO film composite gel base layer using the solution obtained in steps 3) and 4) as the printing material, wherein the vascularization-promoting solution is used as the vascular network printing material and the matrix solution is used as the matrix printing material. The printing and UV curing are performed to form a composite gel surface layer with a vascularized pre-network, and angiogenesis is cultured in vitro at 37°C to obtain a composite artificial gel periosteum containing a vascularized network.

2. The method for preparing the GO membrane-enhanced vascularized network composite artificial gel periosteum material according to claim 1, characterized in that: In step 1), the GO concentration in the coating liquid is 0.05-0.1wt%, and the volume ratio of ethanol to water is 1:9-1:7; the thickness of the GO film is controlled to be 50-200μm.

3. The method for preparing the GO membrane-enhanced vascularized network composite artificial gel periosteum material according to claim 1, characterized in that: In step 2), the concentration of the HAMA solution is 5-7.5 wt %, and a photoinitiator is added with a concentration of 0.1-0.25 wt %.

4. The method for preparing the GO membrane-enhanced vascularized network composite artificial gel periosteum material according to claim 1, characterized in that: In step 3), the preparation method of the mesoporous hydroxyapatite is: mixing a phosphate ion solution, a calcium-containing solution, a surfactant and a template solution, adjusting the pH to 9-11, aging at 35-40°C, collecting the precipitate by centrifugation after aging, and repeatedly washing it with deionized water and ethanol, and drying the obtained product at 50-80°C until the mass is constant to obtain a mesoporous hydroxyapatite material.

5. The method for preparing the GO membrane-enhanced vascularized network composite artificial gel periosteum material according to claim 4, characterized in that: After mixing, the concentration of phosphate ions in the solution is in the range of 0.25-0.35M, the concentration of calcium is 0.45-0.55M, the surfactant is one of phytic acid, SDS, EDTA or citric acid, and the amount added is 4-6 (w / v)% of the total solution. The template solution selected is one of F127 or CTAB, and the concentration is 0.1-0.4g / ml. The centrifugal speed is 5000-10000rpm / min.

6. The method for preparing the GO membrane-enhanced vascularized network composite artificial gel periosteum material according to claim 1, characterized in that: The preparation method of the matrix solution is as follows: using a cyclic ultrasound-freeze-drying loading method to load angiogenic factors in the pores of mesoporous hydroxyapatite, then immersing the obtained mesoporous hydroxyapatite in a dopamine solution to adjust the pH, in situ polymerizing on its surface to form a polydopamine polymer coating layer, and adding the polydopamine polymer coating layer to a HAMA solution containing a photoinitiator and mixing; wherein the cyclic ultrasound-freeze-drying loading method is to add the mesoporous hydroxyapatite to a PBS solution containing angiogenic factors, perform an ultrasound treatment, and then vacuum freeze-dry, and repeat several times to achieve loading.

7. The method for preparing the GO membrane-enhanced vascularized network composite artificial gel periosteum material according to claim 6, characterized in that: The loaded angiogenic growth factor is one or more of VEGF, TGF-β, FGF and PDGF, and the corresponding concentrations are 10-100 ng / mL, 1-10 ng / mL, 1-50 ng / mL and 1-50 ng / mL respectively; the ultrasonic power is 80-100 W, the frequency is 20-40 kHz, and after each ultrasonic loading, the solution is freeze-dried for 2-10 hours at a vacuum degree of 50-100 Pa and a temperature of -20--40° C. The ultrasonic loading and freeze-drying process is repeated 3-5 times; the dopamine solution has a concentration of 6-16 mg / mL, a pH value adjusted to 8.5-11, reacted for 4-8 hours, washed, and freeze-dried for 2-10 hours at a vacuum degree of 50-100 Pa and a temperature of -20--40° C. to obtain dopamine-encapsulated mesoporous hydroxyapatite loaded with angiogenic factors; the HAMA solution has a concentration of 3-5 wt%, wherein the photoinitiator concentration is 0.1-0.25 wt%.

8. The method for preparing the GO membrane-enhanced vascularized network composite artificial gel periosteum material according to claim 1, characterized in that: In the gelatin / HAMA solution, the HAMA concentration is 0.1-0.5wt%, the solution contains a photoinitiator with a concentration of 0.1-0.25wt%, and the gelatin concentration is 1-15wt%; the angiogenic differentiation medium is a basal medium doped with angiogenic factors: the basal medium used is one of M199 basal medium, mixed medium DMEM / F12 and RPMI 1640, and the angiogenic factors used are one or more of VEGF, bFGF, and IGF, and the corresponding concentrations are usually 10-20ng / mL, 5-10ng / mL, and 10-20ng / mL; the bone marrow mesenchymal stem cells added have a density of 1-3×10 7 / mL, and the generations used were P2-P5.

9. The method for preparing the GO membrane-enhanced vascularized network composite artificial gel periosteum material according to claim 1, characterized in that: In the in vitro angiogenesis culture, the basal culture medium used is one of M199 basal culture medium, mixed culture medium DMEM / F12 and RPMI 1640, and the angiogenic factors used are one or more of VEGF, bFGF, and IGF; the culture is carried out in an incubator at 37° C. and 5% CO 2 for 7-14 days.

10. The GO membrane-reinforced composite artificial gel periosteum material containing a vascularized network prepared by the method according to any one of claims 1 to 9.